2005
DOI: 10.1097/01.mao.0000185059.66715.e6
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of Bilateral Same-Day Surgery for Bilateral Perforated Chronic Otitis Media

Abstract: Bilateral same-day surgery for bilateral perforated chronic otitis media is possible if operative indications are considered. Furthermore, it will help patients save time and money.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 7 publications
1
10
1
Order By: Relevance
“…The take rate of 96% is in agreement with international standards of unilateral tympanoplasty type I [8] but not in accordance with three previous studies showing that the presence of bilateral perforations adversely influence the success rate [9][10][11]. No adverse influence was noted in the two previous studies on bilateral surgery, in which the take rate was 91% in the study by Mitchell et al [4] of fat myringoplasty and 85% in the study of Katsura et al [5] of 17 patients operated by underlay techniques.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The take rate of 96% is in agreement with international standards of unilateral tympanoplasty type I [8] but not in accordance with three previous studies showing that the presence of bilateral perforations adversely influence the success rate [9][10][11]. No adverse influence was noted in the two previous studies on bilateral surgery, in which the take rate was 91% in the study by Mitchell et al [4] of fat myringoplasty and 85% in the study of Katsura et al [5] of 17 patients operated by underlay techniques.…”
Section: Discussionsupporting
confidence: 60%
“…However, no data on hearing impairment caused by ear canal packing are retrievable from the literature. Only two international papers focus on the results and feasibility of bilateral tympanoplasty type I [4,5], Mitchell et al [4] reported good results of bilateral simple fat myringoplasty This paper documents the results of bilateral procedures in 14 patients (28 ears) operated by the inlay technique, with use of temporalis fascia (28.5%) and fascia lata [6] (71.5%) as graft material. The treatment strategy pertaining to patient selection criteria, perioperative decision making, and postoperative ear canal packing is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Only two international papers focus on the results and feasibility of bilateral myringoplasty/tympanoplasty type I, 4,5 although several publications document that this procedure is indeed performed occasionally in other centers 6–8 . Mitchell et al 4 reported good results of bilateral simple fat myringoplasty in 28 children, and Katsura et al 5 evaluated 17 patients operated by underlay techniques, either transcanal or through a retroauricular approach. This paper documents the results of bilateral procedures in 26 patients (52 ears) operated transcanal primarily by onlay technique for tympanic membrane perforations caused by chronic otitis media.…”
Section: Introductionmentioning
confidence: 99%
“…Controversy remains as to whether the size of perforation influences the success rate [1] [2]. The transcanal method of simple underlay myringoplasty using fibrin glue was developed in Japan [3] [6]. We performed the simple underlay myringoplasty using this technique only for dry, small-sized perforations.…”
Section: Discussionmentioning
confidence: 99%
“…The same surgeon performed tympanoplasty under general anesthesia using the retroauricular approach. Surgical procedures comprised the underlay technique, harvesting the temporalis fascia as a graft material, and application of fibrin glue [3]. We used the χ 2 test to compare postoperative success rates, and logistic regression analysis to identify factors affecting reperforation.…”
Section: Methodsmentioning
confidence: 99%